AMPK: a balancer of the renin–angiotensin system. Issue 9 (3rd September 2019) - Liu, Jia; Li, Xuan; Lu, Qingguo; Ren, Di; Sun, Xiaodong; Rousselle, Thomas; Li, Ji; Leng, Jiyan
Abstract : The renin–angiotensin system (RAS) is undisputedly well-studied as one of the oldest and most critical regulators for arterial blood pressure, fluid volume, as well as renal function. In recent studies, RAS has also been implicated in the development of obesity, diabetes, hyperlipidemia, and other diseases, and also involved in the regulation of several signaling pathways such as proliferation, apoptosis and autophagy, and insulin resistance. AMP-activated protein kinase (AMPK), an essential cellular energy sensor, has also been discovered to be involved in these diseases and cellular pathways. This would imply a connection between the RAS and AMPK. Therefore, this review serves to draw attention to the cross-talk between RAS and AMPK, then summering the most recent literature which highlights AMPK as a point of balance between physiological and pathological functions of the RAS.